Foliar Treatments of 2,4-Dichlorophenoxyacetic Acid for Control of Common Scab in Potato Have Beneficial Effects on Powdery Scab Control - Hannah Katherine Thompson; Robert Stephen Tegg; Ross Corkrey; Calum Rae Wilson (The Scientific World Journal)
Prior studies have shown that applications of the synthetic auxin 2,4-dichlorophenoxyacetic acid (2,4-D) to the foliage of potato plants can reduce common scab. Here field and glasshouse trials suggest that 2,4-D foliar treatments may also reduce the biologically distinct tuber disease, powdery scab. Significant correlations between suppression of common and powdery scab from the field trials suggested an interaction between the two diseases or possible additional broad spectrum mechanisms of enhanced defence against pathogen invasion provided by 2,4-D treatment.